Minimizing drilling thrust force for HFRP composite by optimizing process parameters using combination of ANOVA Approach and S/N ratios analysis - Maoinser, M.A. (EDP Sciences, 2014)
Drilling hybrid fiber reinforced polymer (HFRP) composite is a novel approach in fiber reinforced polymer (FRP) composite machining studies as this material combining two different fibers in a single matrix that resulted in considerable improvement in mechanical properties and cost saving as compared to conventional fiber composite material. This study presents the development and optimized way of drilling HFRP composite at various drilling parameters such as drill point angle, feed rate and cutting speed by using the full factorial design experiment with the combination of analysis of variance (ANOVA) approach and signal to noise (S/N) ratio analysis. The results identified optimum drilling parameters for drilling the HFRP composite using small drill point angle at low feed rate and medium cutting speed that resulted in lower thrust force. Â© 2014 Owned by the authors, published by EDP Sciences.